1967
DOI: 10.1111/j.1440-1754.1967.tb01689.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of the Seasonal Variation of Asthma to the Weather: An Australia-Wide Survey

Abstract: SYNOPSIS The monthly variation in the incidence of asthma is closely related to temperature. This study, based on the analysis of admissions to children's hospitals throughout Australia, confirms, for a wide range of climates, observations previously reported from Brisbane. The relation is twofold. In the months which normally have a mean temperature below 70°F (21.1°C), asthma increases with increase in temperature. When the temperature exceeds 70°, asthma decreases with increase in temperature, and this is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Rainfall may also create an aerosol rich in allergens, thus increasing their penetration into the bronchi [29]. Coloured basidiospores have previously been implicated in autumn asthma and hay fever [17,25,30]. Their strong correlation in this study suggests that their release into the atmosphere in late summer may contribute to the autumn influx of asthmatics [9], but a spurious correlation may conceivably have arisen through similarity of seasonal patterns.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Rainfall may also create an aerosol rich in allergens, thus increasing their penetration into the bronchi [29]. Coloured basidiospores have previously been implicated in autumn asthma and hay fever [17,25,30]. Their strong correlation in this study suggests that their release into the atmosphere in late summer may contribute to the autumn influx of asthmatics [9], but a spurious correlation may conceivably have arisen through similarity of seasonal patterns.…”
Section: Discussionmentioning
confidence: 66%
“…Previous attempts to define the association between environmental changes and asthma admissions have relied on descriptive [8]. simple statistical techniques [25] or multivariate analysis [ 14. 18].…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal patterns of grass-growth, airborne pollens, air spora, and house-dust mites were studied intensively in the Brisbane area (Derrick, 1967;Domrow, 1970;Mosa 1965~ 1967~, 1967bRees, 1964); the patterns, usually unimodal, were not convincing. Climatic sequences showed a complex relationship to the seasonal patterns seen in asthma admissions (Derrick, 1965(Derrick, , 1966(Derrick, , 1968(Derrick, , 1972Derrick and Szymanski, 1967). It was shown that maximal asthma attendances occurred in Brisbane when the mean ambient temperature was about 21oc and the dew point about 13.5oc.…”
Section: Introductionmentioning
confidence: 96%